Effect of salt stress on the endogenous salicylic acid content in maize (Zea mays L.) plants - Szalai, Gabriella; Páldi, Emil; Janda, Tibor (Acta Biologica Szegediensis, 2005)
Two-week-old maize plants were treated with 50 or 100 mM NaCl for seven days. Leaves and roots were collected for measurements on salicylic acid and antioxidant enzyme activity on the 1st, 3rd and 7th days of treatment and after four days of recovery. The quantum yield of photosystem II decreased after 7 days in maize plants treated with 100 mM NaCl. There were no changes in the catalase and ascorbate peroxidase activity. The glutathione-S-transferase, glutathione reductase and guaiacol peroxidase activities increased. There were no changes in the level of endogenous free and bound salicylic acid. The free o-hydroxy-cinnamic acid (oHCA) content increased after 7 days in the leaves, while the bound oHCA level increased after 4 days of recovery. It has been concluded that oHCA may play an important role in stress processes.